Remnants of arc-related Mesoarchaean oceanic crust in the Tartoq Group of SW Greenland - Szilas, Kristoffer; Van Hinsberg, Vincent J.; Kisters, Alex. F. M.; Hoffmann, J. Elis; Windley, Brian F.; Kokfelt, Thomas F.; Scherstén, Anders; Frei, Robert; Rosing, Minik T.; Muenker, Carsten (Gondwana Research, 2013)
The Tartoq Group, located in SW Greenland, consists of supracrustal rocks of mainly tholeiitic basaltic composition, including pillow lavas, sills/dykes and gabbros, as well as ultramafic rocks. Metamorphic grade ranges from greenschist fades to granulite facies. The Tartoq Group crops out as a series of blocks and slivers that are imbricated with originally intrusive Mesoarchaean TTG orthogneisses. The supracrustal rocks form part of a SE vergent fold and thrust belt consistent with the imbrication of TTG gneisses and supracrustal rocks along a convergent margin. LA-ICP-MS U-Pb zircon dating of an intrusive TTG sheet yields a minimum age of 2986 +/- 4 Ma for the Tartoq Group. This age is consistent with MC-ICP-MS Lu-Hf and Sm-Nd isotopic whole-rock data for mafic samples from different blocks of the Tartoq Group, which yield errorchron ages of 3189 +/- 65 Ma and 3068 +/- 220 Ma, respectively. The mafic supracrustal rocks of the Tartoq Group have chondrite-normalized REE patterns with La-CN/Sm-CN of 0.67-1.96 and rather flat primitive mantle-normalized multi-element patterns, except for scattered LILE contents, and generally negative Nb-anomalies with Nb/Nb* of 0.26-1.31. Th/Yb varies between 0.06 and 0.47 and Nb/Yb between 0.45 and 4.4 indicative of an arc affinity when compared to rocks from modern settings. The similar geochemistry of the different lithological units, together with their coeval formation, as evident from trace element geochemical trends, supports a co-magmatic origin for the rock assemblage and their formation as imbricated relics of oceanic crust Accordingly, we propose that the Tartoq Group represents remnants of Mesoarchaean oceanic crust, which formed in a suprasubduction zone geodynamic environment (C) 2011 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved.